Comemorando a Bendita Santa: experiências religiosas e práticas festivas na devoção à Santa Cruz dos Milagres – Piauí (1968-1990) / - Santos, Patrícia de Sousa (Universidade do Vale do Rio dos Sinos, 2020)
Divina Santa Cruz dos Milagres, a wooden cross with a little more than one meter of high made from an important tree of the region, the aroeira, is one of those popular devotions of Brazilian northeastern that moves a crowd of believers in their festive periods. The first mention of devotion dates from 1888, when the construction of the first chapel in honor to Bendita Santa Cruz dos Milagres is authorized. In the present thesis, we focus on the period that extends from 1968 to 1990, period of strong effervescence of devotion, pointing our eyes on the subjects who experienced it and gave it multiple meanings, such as the believers, the Catholic Church, traders and some local and regional politicians. From consulting a referential historiography about the theme of popular devotions and religious festivals, we analyzed the peculiarities of this country holy, highlighting the extraordinary cures that made possible the popular sanctification of Santa Lenha, which transformed a village surrounded by hills and cut by rivers in the third largest popular devotion Sanctuary in the northeast. Sanctuary that attracts not only the devotees of Piaui, but also from other states, especially Maranhão, Ceará, Pernambuco and Bahia, who move from their homes in search of graces of the mysterious and miraculous Santa Cruz. We also maintened on the analysis of the attempts of organization of devotion taken, especially by the Church, but, in some circumstances, also promoted by the State, as well as the evidences of devotional maintenance tactics employed by the devotees of the Holy, considering the three main festivals of devotion in the Sanctuary of Santa Cruz dos Milagres as the Festa da Invenção (may), Festa de Exaltação (september) and Encontro dos Santos (october). The sources consulted were the Tomb Books, Letters and Decrees, materials available in the parishes and the Curia of Teresina, documents from the Diocese of Maranhão, as well as photographs that allowed us to observe several moments of the festivities in honor to Santa Cruz, as well to discuss the intentionality of these records.
Keywords: Santa Cruz dos Milagres; Devoção; Religiosidade; Piauí; Santa Cruz dos Milagres; Devotion; Religiosity; Piauí; ACCNPQ::Ciências Humanas::História